Handbook of defence economics - Arrow, Kenneth J (Ed.); Intriligator, Michael D (Ed.) (Amsterdam Elsevier, 1995)
Handbook of Defence Economics is in one volumes and its contents are-Nature of defence economics, International security, World Military Expenditures, Terrorism: Theory and application, Defense Industrial Base Economics of Defense, Economics of Arms Trade
Keywords: MILITARY READINGS-ECONOMIC ASPECTS; MILITARY POLICY-ECONOMIC ASPECTS; WAR-ECONOMIC ASPECTS; DEFENSE INDUSTRIES